Case Series on Perforator Aneurysm: Endovascular Stenting—A Safe Strategy - Sahu, Chandra Dev; Ashpilaya, Ashish (Journal of Clinical Interventional Radiology ISVIR, 2017)
Perforator aneurysms are rare vascular lesions that are infrequently reported in literature, and because of difficult anatomic approach, their treatment and management pose challenges. Given the rarity of these aneurysms, the natural history and ideal approach to treatment has not been established. The authors retrospectively analyzed six patients, age ranging from 16 to 75 years with ruptured perforator aneurysm, four of posterior circulation and two of anterior circulation including clinical characteristics, imaging data, treatment regimen, and outcome. All but two patients presented with the World Federation of Neurosurgical Societies grades I to III and Fisher grade 2 or 3 subarachnoid hemorrhage, and the other two presented with intracerebral bleed in the right gangliocapsular region. Four patients were managed conservatively whereas two basilar perforator aneurysms were treated with endovascular stent. At the last follow-up, the endovascularly treated group of patients demonstrated complete thrombosis of aneurysm with preservation of perforators, and the conservatively managed group showed spontaneous occlusion in one patient, whereas three were lost to follow-up and ultimate outcome remains unknown. The authors report single-center hospital-based experience in six patients, which adds to the scarce published literature that addresses the limited understanding of the natural course and consolidating safe endovascular management of this entity.
Keywords: basilar perforator aneurysm; endovascular stenting; lenticulostriate perforator